Wat is verlossing? ’n Teologies kritiese en kanonies-linguistiese ondersoek - Jacobus D.W. de Koning (HTS Teologiese Studies/Theological Studies)
What is redemption? A theological critical and canonical-linguistic investigation. Was Christ’s atonement necessary? If so, why? What was accomplished, and in what sense is it ‘for us’? These are some of the key questions explored in this study. Rather than proposing yet another atonement model to add to the 13 or more already established, this article offers a fresh contribution by advocating for a canonical-linguistic approach to the question of what happened on the cross. It establishes a more comprehensive understanding of the meaning of Jesus’s death on the cross – an understanding in line with the ongoing divine covenantal drama itself. This article contends that such an approach prevents the richness of divine action from being reduced to a single motive or metaphor. Following a discussion and critique of the two predominant perspectives – penal substitution, and relational restoration and liberation – it is suggested that the cross should be understood as the final ratification of the covenant and the confirmation of the kingdom.